2011
DOI: 10.3858/emm.2011.43.4.024
|View full text |Cite
|
Sign up to set email alerts
|

Silencing IL-23 expression by a small hairpin RNA protects against asthma in mice

Abstract: To determine the impact of IL-23 knockdown by RNA interference on the development and severity of ovalbumin (OVA)-induced asthmatic inflammation, and the potential mechanisms in mice, the IL-23-specific RNAi-expressing pSRZsi-IL-23p19 plasmid was constructed and inhaled into OVA-sensitized mice before each challenge, as compared with that of control mice treated with alum or budesonide. Inhalation of the pSRZsi-IL-23p19, significantly reduced the levels of OVA-challenge induced IL-23 in the lung tissues by nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…IL-23 was not different between groups, which may be due to the time interval investigated or represents a distinction from other lung inflammatory models such as asthma whereby IL-23 and IL-17A are important in the enhancement and maintenance of eosinophilic and neutrophilic inflammatory responses. 2427 A similar Th1/Th17 response was demonstrated following repetitive PGN exposures, supporting a role for microbial components like PGN in driving organic dust-induced airway inflammatory responses. Our findings of a mixed Th1/Th17 response would be consistent with observations in smoking subjects with chronic obstructive lung disease (COPD).…”
Section: Discussionmentioning
confidence: 68%
“…IL-23 was not different between groups, which may be due to the time interval investigated or represents a distinction from other lung inflammatory models such as asthma whereby IL-23 and IL-17A are important in the enhancement and maintenance of eosinophilic and neutrophilic inflammatory responses. 2427 A similar Th1/Th17 response was demonstrated following repetitive PGN exposures, supporting a role for microbial components like PGN in driving organic dust-induced airway inflammatory responses. Our findings of a mixed Th1/Th17 response would be consistent with observations in smoking subjects with chronic obstructive lung disease (COPD).…”
Section: Discussionmentioning
confidence: 68%
“…To date, the contribution of IL-23 and IL-17 to asthma is controversial, with different studies proposing either a pathogenic (Haworth et al, 2008;Li et al, 2011;Wakashin et al, 2008) or a protective role (Schnyder-Candrian et al, 2006). Wang et al (2013) reported that IL-17 has a pathogenic role in this wellestablished mouse model of AR, and its effects are limited to the Th2 responses, nasal neutrophil and eosinophil infiltration.…”
Section: Discussionmentioning
confidence: 97%
“…The ability of RNAi to inhibit virulent gene expression has been widely used to treat a variety of diseases (33)(34)(35). Also, a number of studies have reported that RNAi can be used in DCs to diagnose and treat bronchial asthma (36)(37)(38)(39). Darcan-Nicolaisen et al (40) discovered that the two major signs of allergic asthma in the OVA-induced asthma mouse model, which are airway inflammation and hyperactivity, were significantly ameliorated by signal transducer and activator of transcription 6 (STAT6) silencing in airway epithelial cells using the administration of siRNA nose drops.…”
Section: Discussionmentioning
confidence: 99%